Influence of Monomer Systems on the Bond Strength Between Resin Composites and Polymerized Fiber-Reinforced Composite upon Aging - Khan Aftab A.; Mohamed Badreldin; Al-Shamrani Sultan Saleh; Ramakrishnaiah Ravikumar; Perea-Lowery Leila; Säilynoja Eija; Vallittu Pekka K. (QUINTESSENCE PUBLISHING CO INC, 2022)
Purpose: This study examined the influence of different monomer systems on the tensile bond strength between a resin composite and a polymerized fiber-reinforced composite (FRC). The influence of the age (shelf-life) of the FRC prepreg (reinforcing fiber pre-impregnated with a resin system) before preparing the FRC substrate for the bonding test was also assessed.Materials and Methods: Semi-interpenetrating polymer network (semi-IPN)-based glass FRC prepregs were aged for various durations (1, 1.5, and 3 years) at 4 degrees C before being used to prepare FRC substrates via light polymerization. Four groups of aged prepregs were prepared through different treatments with: 1. no primer; 2. a dimethacrylate-based adhesive primer; 3. a universal primer; and 4. a specific composite primer. Subsequently, a resin composite luting cement was applied on the treated FRC substrates and cured with light. The water sorption of the FRC-composite specimens was determined. Then, the differences in the tensile bond strength were evaluated using ANOVA (p <= 0.05).Results: There were significant differences in the tensile bond strength between the composite cement and the FRC according to the primer used (p < 0.001), aging time (p < 0.001), and their interactive effect (p < 0.001).Conclusion: The monomers of the universal primer demonstrated the best ability to diffuse into the semi-IPN structure of the polymer matrix of FRC. This improved the interfacial bond strength between the composite cement and the FRC substrate.